2021
DOI: 10.1136/jitc-2021-002484
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect immune effects of CMP-001, a virus-like particle containing a TLR9 agonist

Abstract: BackgroundCMP-001, also known as vidutolimod, is a virus-like particle containing a TLR9 agonist that is showing promise in early clinical trials. Our group previously demonstrated that the immunostimulatory effects of CMP-001 are dependent on an anti-Qβ antibody response which results in opsonization of CMP-001 and uptake by plasmacytoid dendritic cells (pDCs) that then produce interferon (IFN)-α. IFN-α then leads to an antitumor T-cell response that is responsible for the in vivo efficacy of CMP-001. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Figure 7 A involved addition of soluble anti-Qβ to a sample containing a set amount of vidutolimod allowing for development of immune complex in the sample while Figure 7 B involved addition of varying amounts of immune complex itself. We previously reported that uptake of antibody-coated vidutolimod by monocytes is significantly higher than that of pDCs even though pDC uptake is responsible for the resulting production of Type I Interferon [ 3 ]. There is likely competition for uptake of vidutolimod in the experiments illustrated in Figure 7 A between monocytes and pDCs that impacts on TLR9 agonist activation of pDCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 7 A involved addition of soluble anti-Qβ to a sample containing a set amount of vidutolimod allowing for development of immune complex in the sample while Figure 7 B involved addition of varying amounts of immune complex itself. We previously reported that uptake of antibody-coated vidutolimod by monocytes is significantly higher than that of pDCs even though pDC uptake is responsible for the resulting production of Type I Interferon [ 3 ]. There is likely competition for uptake of vidutolimod in the experiments illustrated in Figure 7 A between monocytes and pDCs that impacts on TLR9 agonist activation of pDCs.…”
Section: Resultsmentioning
confidence: 99%
“…This uptake leads to robust production of Type 1 Interferon by pDCs. Monocytes phagocytose more anti-Qβ-coated vidutolimod particles on a per cell basis than do pDCs which, in the context of a Type 1 Interferon inflammatory milieu, enhances their ability to induce T cell proliferation [ 3 ]. The result of these changes is generation of a T-cell dependent anti-tumor immune response [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A/D- and P-type CpG ODNs are potent type I IFN inducers, because the higher structure formed by base paring between their palindromic sequences causes their localization to early endosome that is prerequisites for robust type I IFN induction 9 11 . A general challenge for their clinical application is that their higher structure results in aggregation, while CpG-A ODN designated as CMP-001 that is packaged in a virus-like particle has been developed and tested in clinical trials 12 , 13 . B/K- and C-type CpG ODNs are also applied for clinical use, and among them, the B/K type has been the most extensively studied 9 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The patient experienced regression of all treated cutaneous lesions, in addition to 50% regression of distant metastases. 6 Some recent examples of intratumoral treatment in melanoma includes CMP-001, a bacteriophage virus-like particle (VLP) loaded with A-type CpGs (NCT02680184/NCT03084640, formerly called QßG10 7 ) without any tumor antigens. This therapy is currently being examined in combination with systemic anti-programmed cell death protein-1(PD-1) in several clinical trials for patients with advanced melanoma with previous resistance to anti-PD-1 treatment.…”
Section: Introductionmentioning
confidence: 99%